Gambaran Keluhan Subjektif dan Penilaian Risiko Ergonomi Menggunakan Metode NBM dan ROSA Pada Pengguna Komputer di Kantor Pusat PT.XYZ - Norus Sholeha; Ratna Ayu Ratriwardhani; Muslikha Nourma Rhomadhoni; Friska Ayu (Peneliti.net, 2022)
Although it has a good impact on work efficiency and effectiveness, the use of computers in office workers also has aspects that can pose an ergonomic risk, namely musculoskeletal disorders (MSDs). To describe the complaints of MSDs and the level of ergonomic risk in PT. XYZ employees can use the NBM and ROSA methods. This research is a quantitative descriptive with an observational and cross sectional approach. The population of this research is employees of the head office of PT. XYZ working on a computer. The sample collection technique used is stratified random sampling according to the inclusion and exclusion criteria and data collection is done by filling out the Nordic Body Maps (NBM) questionnaire, direct observation and documentation. The results of the study based on the distribution of MSDs complaints and their percentages showed that the level of complaints often experienced by workers was on the left shoulder, buttocks, right forearm and fingers of the right hand. Furthermore, the measurement of the level of ergonomic risk using the ROSA method got the results of 52 people including the category of moderate risk level and 4 people belonging to the category of high risk level. In conclusion, the description of subjective complaints and the level of ergonomics risk on respondents needs to be considered and further corrective actions such as improvement of work stations and work postures of employees and socialization of office ergonomics to reduce the level of ergonomics risk using posters.